Micah - Zvi, Ehud Ben; (1951-...) (U.S.A, 2000)
The Forms of the Old Testament Literature Series has long been acknowledged as a unique and valuable commentary on the Old Testament. The volumes in the FOTL series are specifically concerned to explore the structure, genre, setting, and intention of each type of biblical literature so the fullest possible meaning of Scripture can be uncovered. This new addition to the FOTL commentary series presents a complete form-critical analysis of the book of Micah. Ehud Ben Zvi looks at how Micah was read by its ancient audience and explores the social setting that stands behind it. Emphasis is placed on the construction of the past, on the images of the future, and on the relevance of both of these to the present of the community or communities of readers for whom the book was intended. His various lines of investigation lead to a deeper understanding of Micah and its enduring message.
Keywords: Bible OT Micah--Criticism, interpretation, etc